2021
DOI: 10.1021/acsomega.0c06032
|View full text |Cite
|
Sign up to set email alerts
|

Wooden Activated Carbon Production for Dioxin Removal via a Two-Step Process of Carbonization Coupled with Steam Activation from Biomass Wastes

Abstract: A two-step process of carbonization coupled with steam activation was proposed for wooden activated carbon production from four kinds of biomass waste materials. The TG-FTIR results show that the carbonization process started at around 250 °C and finished at 500 °C for the coconut shell, pinewood, and plywood. The carbonization temperature of corn straw was lower than those of the other three samples, which was attributed to the higher concentration of ash content. FTIR results for the volatile compounds durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It indicated that too much steam would lead to over activation and the decline of BET specific surface area. We et al 36 also reported similar results for steam activation of pinewood. The steam activation of char is a typical gasification process.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It indicated that too much steam would lead to over activation and the decline of BET specific surface area. We et al 36 also reported similar results for steam activation of pinewood. The steam activation of char is a typical gasification process.…”
Section: Resultssupporting
confidence: 73%
“…The steam activation of char is a typical gasification process. The global reactions during char‐steam interaction could be summarized as follows 36,37 : Cfgoodbreak+H2normalOnormalC()Ogoodbreak+H2 normalC()OCfgoodbreak+CO …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 500 °C could be chosen as the carbonization temperature for coconut shell during the two-step activation carbon production. Wei et al 36 also reached a similar conclusion.…”
Section: Resultsmentioning
confidence: 60%
“…Next, steam activation of coconut shell char was conducted. Steam is a kind of typical activation agent during physical activation . The heterogeneous reaction between char and steam (gasification reaction) was controlled by reaction temperature, residence time, and the amount of steam .…”
Section: Resultsmentioning
confidence: 99%
“…11,33–35 Steam, CO 2 , and air (in fact O 2 plays the role) are often used as activation agents in physical activation. 15,36–45 Pores are generated by the oxidation–reduction reactions between the activation agents and carbon matrix during the physical activation process (eqn (1)–(3)). 46 C + H 2 O → CO + H 2 C + CO 2 → COC + O 2 → CO 2 …”
Section: Introductionmentioning
confidence: 99%